Desarrollo del módulo web para la gestión de datos en línea del consumo eléctrico de los usuarios bajo módulo GSM SIM900 de Arduino - Azogue Chisag, Jefferson Anthony (2021)
The present research study is extremely useful since it will innovate the way of collect and manage the electricity consumption data of the residential users of the electrical company EEASA, transforming it to an automatic collection avoiding irregularities in taking the reading, whether these are human errors caused by various.Factors that affect the process of billing electricity. At present, electricity companies at an international level are opting for the measurement intelligent, where the electrical system is directed through an intelligent network wherever It is possible to implement meters according to the technology required by this type of network. The present investigation is viable, since the electric company EEASA has all the economic resources such as your own server, web hosting, residential meters, which will be essential for the development of the web module.